Analysis of the effectiveness of Lepidium meyenii, Solanum tuberosum and Musa paradisiaca species as natural coagulants in the treatment of the Cunas River – Peru - Ambrosio Rosales, Francis Eduardo (2024)
The research aimed to analyze the effectiveness of the skins of Solanum tuberosum (Potato), Musa paradisiaca (Banana), and Lepidium meyenni (Maca) as natural coagulants in the removal of physical and chemical parameters: Total suspended solids (TSS), turbidity, pH, and color, in the water sample obtained from the lower basin of the Cunas River. This study presents a level of explanatory research with experimental design, using the inductive method due to the analysis of samples, pre and posttest. In addition, for the elaboration of natural coagulants from skins of S. tuberosum, M. paradisiaca, and L. meyenni, these skins were obtained from restaurants and street commerce, to later perform the Jar-Test at different doses (25, 50, 75, and 100 ppm) using 4 water samples of 1000 mL for each coagulant. The results were: M. paradisiaca had a total average removal effectiveness of 69.39% with 75 ppm, S. tuberosum had a removal effectiveness of 55.86% with 75 ppm, and finally, L. meyenni had a lower removal effectiveness with a total average of 52.62% with 100 ppm. It is concluded that the natural coagulant of M. paradisiaca has a higher average effectiveness compared to S. tuberosum and L. meyenni.